Pengaruh Citra Destinasi Dan Electronic Word Of Mouth (E-WOM) Terhadap Minat Kunjung Wisatawan Di Simpang Lima Gumul Kediri - Suhartapa; Nur Rafida (STIE Pariwisata API Yogyakarta, 2024)
This research aims to determine the influence of destination image and electronic word of mouth (E-WOM) on tourist interest in visiting the Simpang Lima Gumul Kediri Monument. This research uses quantitative methods with descriptive analysis. The sample taken was 100 respondents and the sampling technique used an approach to simple random sampling. Data analysis in this study used simple linear regression analysis, multiple linear regression analysis, classic assumption test, T test, F test, and coefficient of determination test. The results of the research show that there is a positive and significant influence with a coefficient value of 0,299 on destination image on interest in visiting, there is a positive and significant influence with a coefficient value of 0,555 on electronic word of mouth (E-WOM) on interest in visiting, and there is simultaneous influence of 70,3% on destination destination image and electronic word of mouth (E-WOM) on touris interest in visiting the Simpang Lima Gumul Kediri Monument.